2003
DOI: 10.1177/000348940311201104
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Otitis Media: Clinical Aspects of 12 Cases

Abstract: The clinical features of tuberculous otitis media (TOM) have changed. This study was performed to evaluate changing trends in the clinical manifestations of TOM. We reviewed a series of 12 cases of TOM (13 ears) recently treated at Osaka Prefectural Habikino Hospital. The results showed a mean age of 41 years and a male predominance of 1.4 to 1. Central or total perforations of the tympanic membrane were observed in most cases, but none of the patients had multiple perforations. Nine patients (75%) had active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 17 publications
(3 reference statements)
4
27
0
6
Order By: Relevance
“…CT findings of TOM in this study were soft tissue in the entire middle ear cavity, preservation of mastoid air cells without sclerotic change, and soft tissue extension or mucosal thickening of the external auditory canal (EAC) with intact scutum. These CT findings were consistent or not consistent with other reports [2,3].…”
Section: Discussionsupporting
confidence: 75%
“…CT findings of TOM in this study were soft tissue in the entire middle ear cavity, preservation of mastoid air cells without sclerotic change, and soft tissue extension or mucosal thickening of the external auditory canal (EAC) with intact scutum. These CT findings were consistent or not consistent with other reports [2,3].…”
Section: Discussionsupporting
confidence: 75%
“…A total of 181 cases were operated for chronic suppurative otitis media of which 15 cases were diagnosed as tuberculous otitis media. Hence TBOM accounted for 8.2% of the operated cases of chronic suuppurative otitis media Males are usually more affected than females with a ratio of 1.4:1 as studied by Nishiike S et al but in our study the ratio was 0.8:1 [8]. As supported by Cho et al the highest incidence of the disease in patients is around their thirtees.…”
Section: Discussionsupporting
confidence: 60%
“…Multiple TM perforations are also observed, though they are rare. Nishike et al, reported that none of their patients had multiple perforations, facial nerve palsy or bone erosions [9].…”
Section: Discussionmentioning
confidence: 97%